Numerical RG-time integration of the effective potential: analysis and benchmark - Ihssen, Friederike; Sattler, Franz R.; Wink, Nicolas (Physical review, 2023)
We investigate the renormalization group (RG)-time integration of the effective potential in the functional renormalization group in the presence of spontaneous symmetry breaking and its subsequent convexity restoration on the example of a scalar theory in d=3. The features of this setup are common to many physical models and our results are, therefore, directly applicable to a variety of situations. We provide exhaustive work-precision benchmarks and numerical stability analyses by considering the combination of different discrete formulations of the flow equation and a large collection of different algorithms. The results are explained by using the different components entering the RG-time integration process and the eigenvalue structure of the discrete system. Particularly, the combination of Rosenbrock methods, implicit multistep methods, or certain (diagonally) implicit Runge-Kutta methods with exact or automatic differentiation Jacobians proves to be very potent. Furthermore, a reformulation in a logarithmic variable circumvents issues related to the singularity bound in the flat regime of the potential.